Mobility Characteristics and Safety Practices among Secondary School Students in Oyo, Oyo State, Nigeria. - Olawuwo, Abiodun A.; Alabi, Esther B.; Olawole, Moses O. (Ife Social Sciences Review, 2025)
This study examined mobility characteristics and road safety practices among secondary school students in Oyo, Oyo State, Nigeria. The study utilized both primary and secondary data. Using multi-stage sampling, 399 copies of questionnaire were purposely administered to students from sampled 25 senior secondary schools. Secondary data were obtained from relevant organizations. Data collected were analyzed using descriptive and inferential statistics (Chi-square and t-tests). Findings revealed that walking (43.6%) and motorcycles (22.1%) were the dominant modes of school travel, with 54.1% of students commuting independently. Female students were more likely to be escorted (46%) and use private vehicles or buses, while males walked more frequently (54.3%). Travel distances varied, with 44.4% covering 1–2 km daily, and 60.9% spending up to 30 minutes commuting. Students perceived private cars (Mean=3.44) and school buses (Mean=3.34) as safest, while walking (Mean=2.68) was deemed least safe. Despite risks, most students demonstrated cautious street-crossing behaviours: 78.2% avoided crossing without checking for vehicles, and 73.9% refrained from using mobile devices while crossing. Gender differences in safety practices were statistically insignificant. The study highlighted vulnerabilities in student mobility, including reliance on unsafe transport modes and inadequate pedestrian infrastructure. The study recommended for improved road safety education, enhanced pedestrian facilities, stricter enforcement of traffic laws, and policies promoting safer school transport options. These measures were essential to mitigate risks and align with global road safety objectives for protecting young commuters in rapidly urbanizing regions.